2016
DOI: 10.5114/pjp.2016.65875
|View full text |Cite
|
Sign up to set email alerts
|

The role of Cat -262C/T, GPX1 Pro198Leu and Sod1+35A/C gene polymorphisms in a development of primary open-angle glaucoma in a Polish population

Abstract: The development of glaucoma may be connected with a long-term exposure to oxidative stress caused by free radical (ROS). The main aim of this work was an analysis of associations of Cat-262C/T, GPX1 Pro198Leu and SOD1 35 A/C gene polymorphisms of antioxidant enzymes with a risk of open-angle glaucoma (POAG) in a Polish population. DNA samples collected from 209 patients with POAG and 191 healthy controls were used in this study. Polymorphisms were determined by polymerase chain reaction-restriction fragment le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Similar results were found in an Iran cohort [75] and the Turkish population [76]. In the Polish cohort, the T/T genotype was associated with the progression of open-angle glaucoma, and the C/T genotype carriers had an increased risk for the disease [73]. Studies also aimed to evaluate the association between this variation and diabetes mellitus.…”
Section: Selenoproteins and Their Polymorphismssupporting
confidence: 73%
“…Similar results were found in an Iran cohort [75] and the Turkish population [76]. In the Polish cohort, the T/T genotype was associated with the progression of open-angle glaucoma, and the C/T genotype carriers had an increased risk for the disease [73]. Studies also aimed to evaluate the association between this variation and diabetes mellitus.…”
Section: Selenoproteins and Their Polymorphismssupporting
confidence: 73%
“…Polymorphism of catalase gene in the promoter region (rs1001179) affects transcription factor binding and thus decreases enzymatic activity of catalase leading to increased formation of hydroxyl radicals and elevated risk of asbestosis, breast cancer development, and arsenic-induced hyperkeratosis. 42 Recently, the association between the polymorphisms of CAT gene with glaucoma, 43 ulcerative colitis, 44 diabetes, 45 hypertension, 46 and Alzheimer's disease 47 have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were obtained in Saudi patients with POAG; however, on the basis of the study results, the authors suggested that the C47T SOD2 mutation can be a risk factor for various clinical indices, such as high IOP and severe clinical course ( Abu-Amero et al, 2014b ). The possible link between SOD1 35A/C and the risk of POAG was studied in a Polish population and no association was found ( Malinowska et al, 2016 ). The same study found instead that the C/T genotype of both GPx Pro198 Leu and CAT -262C/T confers major risks to developing POAG.…”
Section: Factors Regulating the Redox Statusmentioning
confidence: 99%